WILD BIRD DISTRIBUTION, DIVERSITY AND VIRAL SURVEILLANCE IN INTERNATIONAL INSTITUTE OF TROPICAL AGRICULTURE, IBADAN (2014)
The distribution and abundance of niche specific bird species tend to narrow and decline due to habitat fragmentation and alteration attributed to human development. Nonetheless, the proximity of free ranging poultry to Wild Birds (WB) hotspots provide increased opportunity for interaction and disease transmission between wild and domestic birds. However, the diversity and viral prevalence of WB have not been fully documented in Nigeria. Therefore, diversity indices and viral prevalence of some WB species in International Institute of Tropical Agriculture, Ibadan, Nigeria were investigated. Line transects and mist-netting techniques were used for the WB survey. Complete randomised design was used to assign nine transects 1 km each in forest, farm and dam. Habitat variables were measured in 200m sections. The habitat types were subdivided into ten types of land-use namely; forest, forest edge, cassava, maize, maize-cassava, citrus-cassava-maize, dam-grassland, dam-gallery forest, rice-paddy and ponds. Transects were surveyed monthly and birds trapped quarterly over 22 months. Surveys were carried out from 5.30 am-12.00 noon and 3.00-6.30 pm. Birds seen or heard were identified to species level with the aid of Helmsfield guide of Western Africa and collection of bird calls. Trapped birds were ringed and biometric measurements taken. Cloacal, oropharyngeal and faecal swabs were collected into virus transport medium. Viral RNA was extracted from swabs and reverse transcription PCR performed to test for some viruses. Bird Species Abundance (BSA), Bird Species Richness (BSR), Bird Species Evenness (BSE), Shannon-Wiener diversity index (H), Simpson's diversity index (D) and Viral Prevalence (VP) were determined. Data was analysed using descriptive statistics and ANOVA at p=0.05. A total of 985 WB in 66 species were trapped with a recapture of 15.3%, while IITA yielded a species richness of 238 species of WB in 61 families. Highest capture from forest, farm and dam were Bleda canicapillus (135), Ploceus nigricollis (38) and Actophilornis africana (12) with recapture of 35.6%, 0% and 8.3% respectively. Streptopelia semitorquata had the highest seasonal sighting index of 36.2±6.7 birds. The BSA (73.5±167.8) was highest in dam, while D (0.3±0.2) was highest in farm. The BSR (9.0±4.5), BSE (0.9±0.1) and H (1.9±0.5) were highest in forest. Conversely, BSA (18.6±13.2) and D (0.1±0.1) were lowest in the forest. In addition, BSR (6.8±4.3) and H (1.4±0.6) were lowest in farm, while BSE (0.8±0.2) was lowest in the dam. Pooling all data, BSR (morning: 8.6±0.4, evening: 7.4±0.8) and H (morning: 1.6±0.1, evening: 1.49±0.2) were higher in the morning, while BSA (morning: 55±13.5 birds, evening: 66.5±45.5 birds) and D (morning: 0.2±0.1, evening: 0.4±0.1) were higher in the evening. The investigated viruses and their prevalence were Newcastle disease, avian influenza, rotavirus, infectious bronchitis, chicken astrovirus, turkey astrovirus I and II with 9.5%, 0%, 0%, 0%, 0%, 0% and 0% respectively. Habitat diversity was responsible for the high bird species diversity. Monocultures such as farms and ponds did not support high levels of diversity and richness of wild bird species. Bird species increased with habitat diversity. Viral prevalence among wild birds was low, suggesting low possibility of disease transmission from them to domestic birds.